Association between school-level attributes and weight status of Ghanaian primary school children - Theodosia Adom; André Pascal Kengne; Anniza De Villiers; Thandi Puoane (BMC, 2019)
Abstract Background Little is known about the impact of the school environmental context on the emerging trend of childhood obesity in Africa. We examined the association of the schools' contextual factors with body mass index (BMI), abdominal obesity and overweight (including obesity) in urban Ghana. Method Using cross-sectional data from 543 school children aged 8-11 years attending 14 primary schools, we applied multilevel logistic regressions and linear regression models to investigate the association of child- and school level attributes with overweight, abdominal obesity, and BMI. Results We observed significant variance of the random effects of schools in BMI (2.65, p <  0.05), abdominal obesity (0.85, p <  0.05), and overweight (1.41, p < 0.05), with school contextual levels accounting for 19.7, 20.6, and 30.0% of the total variability observed in BMI, abdominal obesity and overweight respectively. Attending high socioeconomic (SES) level school, private school and school with increased after-school recreational facilities were associated with higher BMI. Children were more likely to be overweight if they attended a high SES level school, had access to healthful foods at school, and after-school recreational facilities. With regards to abdominal obesity, attending a school with increased physical activity facilities decreased the odds of abdominal obesity; however the odds increased if they attended a school with access to after-school recreational facilities. Conclusion A number of school-level factors were associated with BMI, overweight and abdominal obesity of children in the present study. Our results provide support for improved school environment to reduce overweight.